Praktik Jual Beli Sayur Kubis dengan Sistem Tebasan di Desa Kalitengah Kecamatan Garung Kabupaten Wonosobo Perspektif Akad Jizāf - Nur Hidayatulloh; Muhajir Muhajir; Septian Fiktor Riyantoro (CV. Ulil Albab Corp, 2024)
The practice of buying and selling cabbage vegetables using the slash system has been carried out for generations by the Muslim community in Kalitengah Village, Garung District, Wonosobo Regency. This kind of buying and selling practice is carried out naturally and is not based on knowledge of religious teachings. Researchers are interested in uncovering this phenomenon using a fiqh analysis tool, namely the jizāf contract, because the majority of the Kalitengah village community is Muslim and they must know whether their muamalah activities are in accordance with the Islamic teachings they adhere to or not. This research reveals that the practice of buying and selling cabbage using the slash system carried out by the Muslim community in Kalitengah Village, Garung District, Wonosobo Regency tends to fulfill the jizāf buying and selling agreement. Namely buying and selling which is permitted in the plural by Islamic jurisprudence scholars for objects that cause mashaqqah (difficulty) and has become a necessity for the majority of society because of the ease of doing it.